A Numerical Study for the Self-Propulsion Performance of a Propulsion System Using the Coanda Effect - Jun-Hee Lee; Kwang-Jun Paik; Do-Han Oh (Journal of Marine Science and Engineering)
This study evaluated the performance of a ship propeller numerically using the Coanda effect. The simulations applied a model based on a 6.5K DWT tanker and conducted self-propulsion assessments for three types of propellers: the original propeller, a normal propeller, and a Coanda propeller. The numerical simulations used the unsteady Reynolds-averaged Navier–Stokes (URANS) equations, incorporating the SST k–ω turbulence model. The influence of the additional thrust generated by the Coanda effect on the hull resistance and self-propulsion factors was analyzed. The key findings showed that the Coanda-based propeller achieved efficient propulsion performance by generating additional lift even at low rotational speeds. A self-propulsion analysis showed that the Coanda propeller required approximately 7.8% less delivered power than the original propeller. These results suggest that propulsion systems utilizing the Coanda effect offer superior efficiency and economic advantages over traditional technologies. This study provides critical baseline data for assessing the feasibility of a Coanda propeller, with further validation planned through full-scale ship simulations.